Lifestyle Behaviors and Depressive Symptoms in Chinese Adolescents Using Regression and fsQCA Models - Mei, Songli; Lv, Jianping; Ren, Hui; Guo, Xinmeng; Meng, Cuicui; Fei, Junsong; Yuan, Tongshuang; Yue, Jingyi; Gao, Ren; Song, Qianqian; Zhao, Xixi; Ao, Yu; et al. (Frontiers in Public Health, 2022)
The study was to compare the performance of the regression models and fuzzy set qualitative comparative analysis (fsQCA) models in analyzing the possible effects of sociodemographic variables (age and sex) and lifestyle behaviors (physical activity, sedentary time, sleep duration, physical education class and screen time) on depressive symptoms in adolescents. This cross-sectional surgery was conducted among 726 adolescents in Jilin Province of China, selected by random cluster sampling. The regression model showed that age, physical education (PE) class and sleep duration were associated with depressive symptoms. Meanwhile, the fsQCA models showed that shorter physical activity, PE class and sleep duration as well as longer sedentary and screen time were related to higher levels of depressive symptoms. Both regression and fsQCA models indicated that promoting lifestyle behaviors could affect depressive symptoms. Considering the differences between the two methods, they are not superior to the other method, but complementary and should be used in other studies at the same time.